Effect of Cryopreservation on Micro Structure of Rambutan Embryonic Axis - Chua, Chin Kok (2004)
Nephelium lappaceum or locally known as rambutan is a valuable fruit species in Malaysia with export potential. Due to its recalcitrant seed characteristic,it cannot be preserved under classical storage conditions and thus, cryopreservation offers a promising tool for long-term storage and conservation of its genetic resources.The study on the morphology and anatomy of excised embryonic axes from seeds of rambutan was undertaken to provide a scientific understanding of the material to be cryopreserved and to elucidate the basis of cryopreservationassociated injuries.Histology of the embryonic axis, both longitudinal and transverse sections were carried out which allowed the reconstruction of three dimensional model.The embryonic axis consisted of conical shaped epicotyl and dome shaped radicle.The recommended size for excision of the embryonic axis would be a 3mm cubical block that is made up of an oblong structured inner axis(1.8mm in length) attached to some amount of cotyledonary tissue.Retaining part of the cotyledon with the embryonic axis helped to provide the minimal nutrient supply for the embryonic axis. The three-dimensional model showed the connection of the embryonic axis to the cotyledons.The cotyledonary vessel from the procambium of the radicle appeared to be the umbilical cord of the embryonic axis to the cotyledon. The embryonic axis, in and ex vivo, shared similar growth and development pattern. With adequate moisture, it was able to undergo the normal germination process. Shoot development in in and ex vivo embryonic axis was normal and rapid. Within four days of moisture imbibition,the conical shaped epicotyl had expanded into initial shoot. Growth of trichomes or hairy structures, which presumably could protect the embryonic axis from rapid desiccation and injury, also ensures germination. Dissimilarity occurred when the axis that germinated within the seed (in vivo) developed root cap while those cultured on MS media (ex vivo) did not. However,this characteristic had no adverse effect against a normal germination route.Cryopreservation of recalcitrant seed species is difficult and is often not reproducible. Results reported by Hiew (1991) and Ginibun (2001) were not reproducible in this study in spite of close adherence to the protocol used.Even minor modification of the successful recipe and protocols reported by them did not produce surviving cryopreserved embryonic axis.It is evident in the study that the cells of the embryonic axis were possibly killed by the subzero temperature of the liquid nitrogen. As compared to the severe damage of fresh embryonic axis when directly exposed to liquid nitrogen,the structural damage of the cryopreserved embryonic axis appeared to be minimised after pretreatment by vitrification.This study suggested that the recipe of the vitrification solution used by Ginibun (2001) was not sufficient to reproduce the results reported.However,the potential of vitrification as a pretreatment prior to cryopreservation in liquid nitrogen cannot be discounted.Further study needs to be pursued on the effects of liquid nitrogen on the vitrified cryopreserved embryonic axis of recalcitrant rambutan at the ultrastructural level. Fundamental studies through microscopic work have provided new insight and understanding of the plant material.